2021
DOI: 10.1186/s13613-021-00950-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antibiotic therapy on the prognosis of ventilator-associated pneumonia caused by Stenotrophomonas maltophilia

Abstract: Background Ventilator-associated pneumonia (VAP) caused by Stenotrophomonas maltophilia is poorly described in the literature. However, it has been shown to be associated with increased morbidity and mortality. Probabilistic antibiotic therapy against S. maltophilia is often ineffective as this pathogen is resistant to many antibiotics. There is no consensus at present on the best therapeutic strategy to adopt (class of antibiotics, antibiotic combination, dosage, treatment duration). The aim o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 28 publications
3
10
6
Order By: Relevance
“…Furthermore, the Klebsiella species accounted only for 3.1% of all pathogens, and caused monobacterial cases only. Yet, there are studies of pneumonia that, similar to our findings, have revealed higher mortality in polybacterial cases [21,28,33].…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, the Klebsiella species accounted only for 3.1% of all pathogens, and caused monobacterial cases only. Yet, there are studies of pneumonia that, similar to our findings, have revealed higher mortality in polybacterial cases [21,28,33].…”
Section: Discussionsupporting
confidence: 90%
“…The relatively smaller sample size in that study (only 35 S. maltophilia BSI cases included), with a low statistical power, may have accounted for the insigni cant effect of antibiotic therapy on the outcomes [32]. Among the studies focused on pneumonia caused by S. maltophilia in ICU, some studies revealed that antibiotic therapy may effect the clinical outcomes whereas others showed no such association [20,21,34,35]. The different ICU settings, respiratory copathogen diversity, and a heterogeneous population may explain the inconsistent effects of antibiotic therapy on the clinical outcomes in these studies.…”
Section: Discussionmentioning
confidence: 88%
“…Higher APACHE II scores were also found to be related to an elevated mortality rate in this study cohort, consistent with prior research results [ 20 , 21 ]. For example, Kanchanasuwan et al [ 21 ] and Puech et al [ 22 ] determined that appropriate empirical antimicrobial treatment was related to a significant reduction in 30-day mortality, with higher baseline APACHE II scores serving as an independent predictor of mortality risk. A longer interval between HAP onset and definitive treatment was also associated with a higher risk of death in the present study, highlighting the importance of promptly administering appropriate antimicrobial drugs to most effectively treat S. maltophilia -HAP.…”
Section: Discussionmentioning
confidence: 99%